Doping of Hole Transport Layer PEDOT: PSS with Pentacene for PCDTBT: PCBM Based Organic Solar Cells. (2017) - Sivakumar, G.; Pratyusha, T.; Gupta, D.; Shen, W.
Abstract: Organic photovoltaics are a renewable form of energy with benefits such as solution process ability, low cost environment friendly production methods and flexible substrates. In this paper we discuss about the doping of hole transport layer PEDOT:PSS with pentacene in PCDTBT Poly[N-9′-heptadecanyl-2, 7-carbazole-alt-5, 5-(4′, 7′-di-2-thienyl- organic solar cells using 2′, 1′, 3′-benzothiadiazole)]:PC70BM (phenyl C71 butyric acid methyl ester) based organic solar cell with the device structure (Glass/ITO/PEDOT:PSS doped with pentacene/ PCDTBT:PCBM/ Ca/Al.) The performance characteristics are evaluated by increasing the amount of pentacene and the annealing temperature of the pentacene doped PEDOT: PSS layer. When the amount of pentacene was increased, transmittance is increased which in turn allows more light to reach the active layer. As the annealing temperature is increased, agglomeration of PEDOT: PSS is observed. The films of pentacene-doped PEDOT: PSS were characterized by UV-vis transmittance AFM (atomic force microscopy) and FESEM (scanning electron microscope).